Synergistic effects of anlotinib and DDP on breast cancer: targeting the VEGF/JAK2/STAT3 axis - Zhang, Hongmei; Liu, Chunling; Jin, Ye; Wang, Zheng; Guan, Yi; Jia, Zhenxian; Cui, Tong; Zhang, Zhi; Zhang, Xuemei (Frontiers in Pharmacology, 2024)
Background: Anlotinib, a highly selective inhibitor of VEGFR2, has demonstrated significant antitumor effects in various cancers. However, its potential synergistic effects with DDP (cisplatin) in breast cancer (BRCA) remain to be fully elucidated. This study aims to discover the therapeutic efficacy of anlotinib on BRCA, specifically the synergistic effects with DDP, and to elucidate the underlying molecular mechanisms.Methods: BRCA cells were treated with anlotinib and/or DDP. The proliferation, migration and invasion capabilities of BRCA cells were evaluated using CCK-8 assays, cell cycle distribution, clone formation assays, wound healing assays and transwell assays. Cell apoptosis was detected by flow cytometry technique and Hoechst33342 fluorescence staining. The potential mechanism of anlotinib in the development of BRCA was predicted through bioinformatics analysis, and the mRNA or protein levels were subsequently quantified using qPCR, immunofuorescence and western blot. The anti-breast cancer efficacy of anlotinib was evaluated in vivo using a xenograft tumor model.Our findings reveal that increased VEGFA expression in BRCA patients is associated with poorer prognosis, underscoring the need for targeted therapeutic strategies. We also demonstrate that both anlotinib and DDP independently inhibit BRCA cell growth, migration, and invasion, while their combination exhibits a synergistic effect, significantly enhancing the inhibition of these oncogenic processes. This synergy is further evident through the induction of apoptosis and autophagy in BRCA cells. Mechanistically, anlotinib's effectiveness is linked to its inhibition of the JAK2/STAT3 pathway, a critical axis in BRCA progression. In vivo study further support these results, showing that anlotinib markedly inhibits tumor growth in xenografted mice.This study confirms the efficacy of anlotinib or in combination with DDP and elucidates the mechanism behind anlotinib's effectiveness, highlighting its role in inhibiting the JAK2/STAT3 pathway.